UNDERSTANDING CONTINUED USE OF TAX E-FILLING SYSTEMS: EVIDENCE FROM INDONESIA - Benih Hartanti; Tisya Trilaksana Mawarni; Suluh Agus Hendrawan; Sugeng Suprapto (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2023)
The adoption of electronic tax filing (e-filing) systems has been widely examined; however, less attention has been paid to factors influencing their continued use, particularly in public sector contexts. This study investigates the determinants of intention to use and continued use of Indonesia’s e-filing system by integrating the Technology Acceptance Model (TAM) and the DeLone and McLean Information Systems Success Model, with perceived system security and trust initially incorporated as extensions. Using survey data from 100 individual taxpayers and structural equation modeling with partial least squares (SEM-PLS), the study examines the relationships among perceived ease of use, information system quality, perceived system security, trust, and e-filing usage behavior. The results indicate that perceived ease of use, information system quality, and perceived system security significantly influence both intentions to use and continued use of e-filing, while trust does not function as a significant moderating variable. Information system quality emerges as the strongest predictor of usage behavior. These findings suggest that, in institutionalized e-government systems, continued use is driven primarily by system performance and security rather than by trust. The study contributes to the literature on information system continuance and e-government by highlighting how system quality operates as a key indicator of administrative effectiveness in public digital services.